(3cfGT CHh Sgd aj GdWHs - (3eSYhO Hf eMeO GdSLRj, CHhSgd GdSLRj GdWHjHs ((3eMeO Hf GHj HcQ Hf eMeO GdfSGN s)
(3ChdgG (B:s
(3GdMeO ddg GdeHJOY aj GHJOGFI GdeaUd CdGFI bGd GHh Sgd HTQ Hf jYbhH Hf GSMGb GdeJWHH GdSLRj C(B/(3G HYO aEf GdCejQ CMeO Nda Hf CMeO hde fLO ef GdcJH G deDdaI cGdcfGTGJ s
(3BNQgG (B:s
(3JeJ GdebGdI GdQGHYI ef cJGH GdQSGFd GdWHjI s
(3Vef eLehY , JQJjHgG (B: 2s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs